Relationship Between Pod Characteristics of Some Cocoa Clones (T. cacaoL.) and Their Resistance Response to Cocoa Pod Borer - Agung Wahyu Susilo; Woerjono Mangoendidjojo; Witjaksono . (Indonesian Coffee and Cocoa Research Institute, 2007)
Characteristic study on CPB resistance had been carried out by characterizing mesocarp layer of cocoa pod where egg laying and larva penetration are carried out. For this study, 4 clones were selected which performed different response to CPB, namely resistant clones of KW 514 and ARDACIAR 10, moderately resistant clone of KW 411 and the susceptible clone of RCC 72. Pod samples were classified as young and mature were detached from cocoa collection at the experimental station of Kaliwining, Indonesian Coffee and Cocoa Research Institute in Jember. Characterization was conducted based on microchemical method at the Microtechnique Laboratory of Gadjah Mada University to identify trichome appearance at upper layer of pod, distributed granules of tannin through mesocarp and lignification of the sclerotic. It was characterized that the trichome density performing resistant in which the resistant and moderately resistant clones had more number of trichome density than of the susceptible one. The distributed granules of tannin at young pod showed significant difference among those clones that indicate resistant characteristics. The number of distributed granules of tannin was higher of those the resistant and moderatly resistant clones than of the susceptible clones that were formed both at furrow and at ridge of pod. However, the granules of tannin were distributed more at ridge than at furrow where furrow were preferred by CPB for egg laying. The characteristic differences between the resistant and moderately resistant clones were identified based on the intensity of lignification at sclerotic tissue. The lignified tissue of the resistant clones perform more intensive and more compact than of the moderately resistant clones. Tissue of young pod of the moderately resistant and susceptible clones was not yet lignified. Thickness of lignified tissue at the furrow of resistant clone was higher than of the moderately resistant and susceptible clones. Key words : Theobroma cocoa L.,cocoa pod borer, resistant, mesocarp, sclerotic, trichome, tannin.